DIGITAL MOVEMENT TRENDS OF INDONESIAN YOUTH IN THE NEW NORMAL ERA: TRANSITIONING TO A NEW APPROACH FOR YOUTH COMMUNITY CONTRIBUTION IN SOCIETY - Muhammad Adi Sukma Nalendra; Ria Sapitri; Rini Amadia (LPPM ITEBA, 2023)
The global spread of the Covid-19 pandemic has not only had an impact on the business world, but also had a major impact on the world of education, social and cultural. This also has an impact on the implementation of community social activities and social communities in the community in carrying out their activities such as conducting seminars online. Responding to this, the ITEBA research team is always committed to contributing to the development of youth in Batam City by providing material support in various online activities carried out by the community and youth in Batam City. In cooperation with the Ikatan Pemuda Karya (IPK) Pulau Bawah organization, the ITEBA team was also active in the implementation of the COVID webinar, education through posters and giving out groceries in several locations in Batam. A total of 17 districts in Batam were helped by the donation of groceries and the CSR of Pulau Bawah Resort and ITEBA. The activities carried out in addition to helping the economy of people affected by COVID also build cooperation and initiatives of the Ikatan Pemuda Karya organization during the pandemic.